(untitled) (International Association of Biologicals and Computational Digest, 2022)
The field survey for documentation of Ethno-medicinal plants of different villages of dang’s district was carried out during Octember-2015 to April-2016. Study mainly Interviewed 10 traditional healers of different villages like Borigavtha, Jhawda, Galkund, Bhapkhal, Ranpada, Nanapada, Sakarpatal and Bardipada. Almost about 85 different plant species were used as medicine for querying different diseases like Stomach pain, Fracture, Fever, Skin disease, Ulcer, Vomiting, Wounds, and Diabetes and for Cattle diseases. Roots and Bark was used in higher amount as a part used for medicine